2021
DOI: 10.2174/1874325002115010041
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Heel Pad Avulsion in a Pediatric Patient

Abstract: Introduction: Heel pad injuries can have devastating and debilitating consequences. All efforts to primarily reapproximate the heel pad should be undertaken. Reconstruction of the heel pad can often require multiple complex surgeries including microvascular flaps and tissue transfers. There is a paucity of successful techniques for primary repair in the literature. Case Presentation: In this case report, we describe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…There are various documented methods of heel pad primary repair including K-wire or Schanz pin fixation as well as salvage with split-thickness skin grafting 1-4 . In addition, there is one case report of successful heel pad repair using suture and sterile button fixation by Kelly et al in a pediatric patient 5 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There are various documented methods of heel pad primary repair including K-wire or Schanz pin fixation as well as salvage with split-thickness skin grafting 1-4 . In addition, there is one case report of successful heel pad repair using suture and sterile button fixation by Kelly et al in a pediatric patient 5 .…”
Section: Discussionmentioning
confidence: 99%
“…The use of a quilted technique with suture that is passed through the skin, periosteum, and bone allows for a strong anchor to which sterile buttons may be affixed over the top. The sterile buttons allow for a greater surface area at the suture skin interface, which then disperses the force across the heel pad 5 . In this report, sterile buttons were used to affix the heel pad to the calcaneus; however, other cadaveric studies have demonstrated effective use of sterile buttons for fixation of flexor digitorum profundus repair.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations